2022
DOI: 10.1155/2022/1805689
|View full text |Cite|
|
Sign up to set email alerts
|

A Statistical Prediction Model for Healthcare and Landslide Sensitivity Evaluation in Coal Mining Subsidence Area

Abstract: The purpose of this study is to compare the results of the frequency ratio (FR) model with the weight of evidence (WOE) and the logical regression (LR) methods when applied to the landslide susceptibility evaluation in coal mining subsidence areas. Key geological disaster prevention and control areas are taken as the research areas. Field investigation is carried out according to the recorded landslide disaster points in the past five years, and 86 landslide disaster points are determined from the remote sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Through sensitivity subject curve (ROC) testing, the AUC of the evaluation model proposed in this study is 0.863. According to the experimental schemes of different researchers, the AUC of landslide susceptibility evaluation models is generally around 0.7-0.91 [12,[37][38][39][40]. The accuracy of the predictive model is classified into five categories, and a value above 0.7 indicates that the predictive model is good [41].…”
Section: Discussionmentioning
confidence: 99%
“…Through sensitivity subject curve (ROC) testing, the AUC of the evaluation model proposed in this study is 0.863. According to the experimental schemes of different researchers, the AUC of landslide susceptibility evaluation models is generally around 0.7-0.91 [12,[37][38][39][40]. The accuracy of the predictive model is classified into five categories, and a value above 0.7 indicates that the predictive model is good [41].…”
Section: Discussionmentioning
confidence: 99%
“…There have been plenty of excellent works in landslide susceptibility evaluation (LSE, also called as landslide susceptibility mapping, LSM), and a variety of algorithms were suggested or employed in these works. These diverse methods typically consist of logic regression (Shou and Chen, 2021;Ge et al, 2022), weights of evidence (Goyes-Penafiel and Hernandez-Rojas, 2021), fuzzy logic (Nwazelibe et al, 2023), Analytical Hierarchy Process (AHP) (Wadadar and Mukhopadhyay, 2022), Information value (Es-Smairi et al, 2022), statistical index model (Berhane and Tadesse, 2021), support vector machine (SVM) (Daviran et al, 2022), random forest (RF) (Taalab et al, 2018), convolutional neural network (CNN) (Aslam et al, 2022), recurrent neural network (Ngo et al, 2021), and ensemble learning [such as boosted regression tree-random forest (Chowdhuri et al, 2021), random forest-cusp catastrophe model (Sun et al, 2022), CNN with metaheuristic optimization (Hakim et al, 2022), and so on]. Hakim et al (2022) suggested two ensemble deep learning models including the ensemble of CNN and grey wolf optimizer (GWO) and the complex model of CNN and imperialist competitive algorithm (ICA).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%